A Charlie Brown Christmas - Mendelson, Lee; Melendez, Bill; Schulz, Charles M. (Charles Monroe), 1922-2000; Robbins, Peter, 1956-; Shea, Chris, 1958-; Dryer, Sally, 1957-; Steinberg, Kathy; Guaraldi, Vince; United Feature Syndicate; Warner Home Video (Firm) (Warner Home Video, 2014)
Feeling that the Christmas message is getting lost amid all the seasonal glitter, Charlie Brown has the blues. But when he takes Lucy's advice and tries desperately to organize a Christmas pageant, nothing seems to go his way. Join Charlie Brown and the Peanuts gang as they discover for themselves the true meaning of Christmas.
Originally broadcast as a television special in 1965.
Based on the comic strip by Charles M. Schulz.
"Peanuts by Schulz"--Container.
Special features: It's Christmastime again, Charlie Brown (television special) (1992) (23 min.); A Christmas miracle : the making of a Charlie Brown Christmas (featurette) (2008) (16 min.).
Composer/conductor, Vince Guaraldi ; editor, Robert T. Gillis.
Voices, Peter Robbins, Christopher Shea, Sally Dryer, Kathy Steinberg.
Keywords: Brown, Charlie -- (Fictitious character) -- Juvenile films; Brown, Charlie -- (Fictitious character) -- Drama; Christmas -- Juvenile films; Christmas -- Drama; Brown, Charlie (Fictitious character); Christmas; Christmas television programs; Children's television programs; Animated television programs; Television adaptations; Television specials; Fiction television programs; Video recordings for the hearing impaired; Drama; Films; Juvenile works